Measuring and managing the value-at-risk of a stocks and bonds portfolio - Cebotari, Radu (2023)
The Economic Capital (EC) can be defined as the the capital at risk that derives from investment activities and it is measured by the industry standard risk measurement metric: Value-at-Risk (VaR). Given a pre-defined maximum value for the EC, it is around this target that risk management decisions can be formulated. This work measures and manages the VaR of a portfolio comprised of equities and bonds from the U.S. and European markets such that it does not surpass the pre-defined target. Given the variety of VaR models available, to conclude on which model provides the most accurate measurements for the portfolio in this work, 16 different models are computed and their performance is assessed through a backtest. Using the best performing model, the VaR of the portfolio is measured daily and managed through an equity exposure hedging strategy for a period of one year. To assess the results of the strategy, the Return on Risk-Adjusted Capital (RORAC) performance metric is used. Results show that the equity exposure hedging strategy was successful in limiting the maximum VaR and in safeguarding against further losses.